THE RELATIONSHIP BETWEEN ABILITY OF LIFE AND SELF CARE IN POST-HEART ATTACK PATIENTS - Fauziansyah, Ahmad; Miftahul Munir; Mohammad Fahrul Arifin; Wanda Astia (JURNAL KESEHATAN, SAINS, DAN TEKNOLOGI (JAKASAKTI), 2025)
Self-care is an effort to develop a health system in which patients and their families participate in their care. Patients and families are partners in making health decisions and ensuring that these decisions align with the goals of improving health and sustaining life. Self-care in post-stroke patients includes adherence to treatment, maintaining physical health (diet, avoiding smoking, alcohol consumption, and consuming high-cholesterol foods), managing stress, consulting with healthcare professionals, and providing social support for self-care. This study is a non-experimental study with a correlational design using a cross-sectional approach. The population was 200 post-stroke patients in the Tuban Community Health Center (Puskesmas) working area. The sample size was 130 respondents selected using cluster random sampling. The independent variable was quality of life, while the dependent variable was self-care. The research instrument used was a questionnaire measured using the Spearman rank sum test. The statistical test results using the SPSS application yielded a significance value of 0.000, indicating p < 0.05, which means that H1 is accepted. Therefore, it can be concluded that there is a significant relationship between quality of life and self-care in post-stroke patients in the Tuban Community Health Center work area. To increase insight into self-care quality of life in post-stroke patients in the Tuban Community Health Center work area